THE PRINCIPLE OF IMMEDIACY IN ABBREVIATED CRIMINAL PROCEDURE ACCORDING TO THE 2011 CRIMINAL PROCEDURE CODE OF SERBIA (Part One: Structural and Modal Aspects of Immediacy): (Part One: Structural and Modal Aspects of Immediacy) - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The subject of our research is the principle of immediacy in abbreviated criminal procedure under the 2011 Criminal Procedure Code (CPC) of Serbia. This article presents the results of the first part of the research, analyzing the structural and modal aspects of the principle of immediacy. The structural aspect is established in Article 419, Paragraph 1 of the CPC, which stipulates that the court can base its verdict only on evidence presented at the main trial. This rule applies without exception, both in general criminal proceedings and in abbreviated procedures.The modal aspect of immediacy mandates the direct presentation of evidence at the main trial. In abbreviated proceedings, the provisions of general criminal procedure apply accordingly, both regarding the basic rule and the permissible exceptions to this aspect. This involves certain adjustments, such as the decision on indirect evidence presentation being made by a single judge rather than a trial panel. Furthermore, Article 404 of the CPC, which allows for evidence to be presented outside the main trial, constitutes a departure from the modal aspect of immediacy in general proceedings but not in abbreviated proceedings, precisely because such actions are undertaken by a single judge.The most significant deviation from the rule of direct evidence presentation is found in Article 406 of the CPC. By equating non-judicial and judicial evidence, this provision contributes to a more radical distortion of the modal aspect of the principle of immediacy. A systematic interpretation of the CPC provisions reveals that a similar risk of evidence from the pre-investigation phase spilling over into the main proceedings exists in abbreviated procedures, despite the absence of an investigative phase.
Keywords: Keywords: principle of immediacy, abbreviated proceedings, direct evidence presentation, review of statements recorded in minutes